2002
DOI: 10.1038/ncb870
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-induced microtubule assembly mediated by TPX2 is required for spindle formation in HeLa cells

Abstract: In Xenopus laevis egg extracts, TPX2 is required for the Ran-GTP-dependent assembly of microtubules around chromosomes. Here we show that interfering with the function of the human homologue of TPX2 in HeLa cells causes defects in microtubule organization during mitosis. Suppressing the expression of human TPX2 by RNA interference leads to the formation of two microtubule asters that do not interact and do not form a spindle. Our results suggest that in vivo, even in the presence of duplicated centrosomes, spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
303
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(340 citation statements)
references
References 37 publications
32
303
2
Order By: Relevance
“…These are molecules of the chromosomal passenger complex (CDCA8 and Aurora kinase B; ref. 34 37,38), and several members of the kinesin superfamily of mitotic motor proteins involved in spindle function and cytokinesis (KIFC1, KIF23, KIF11, and KNSL7; refs. 39 -45).…”
Section: Discussionmentioning
confidence: 99%
“…These are molecules of the chromosomal passenger complex (CDCA8 and Aurora kinase B; ref. 34 37,38), and several members of the kinesin superfamily of mitotic motor proteins involved in spindle function and cytokinesis (KIFC1, KIF23, KIF11, and KNSL7; refs. 39 -45).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that TPX2 overexpression induces the amplification of centrosomes and results in DNA polyploidy (9). TPX2 also serves a crucial role in the proliferation of various tumor cells (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…TPX2 also serves a crucial role in the proliferation of various tumor cells (10,11). TPX2 expression is closely regulated by the cell cycle, and exhibits particularly high expression in proliferating cells transitioning between the G 1 and S phase (12)(13)(14). Certain studies have demonstrated that the TPX2 gene, in addition to elevated gene copy numbers, is frequently identified in various human malignancies, including lung carcinoma (15), salivary gland cancer (16), esophageal cell carcinoma (17) and breast cancer (18).…”
Section: Introductionmentioning
confidence: 99%
“…A third possibility is that there are new MTs that grow from the chromosomes and become incorporated into the K-fiber bundles (Khodjakov et al, 2003). The MTs that grow from the chromosomes may quickly become coated with HURP or with TPX2, two specialized MT-associated proteins that have been implicated in chromosomemediated spindle assembly (Gruss et al, 2002;Koffa et al, 2006;Sillje et al, 2006;Tulu et al, 2006;Wong and Fang, 2006;Casanova et al, 2008), such that their overall dynamics are more consistent with the stabilized MTs present in a K-fiber. This possibility is consistent with our observation in Figure 5, G and H, where as the concentration of paclitaxel is increased, the percentage of MTs in the slow phase is increased.…”
Section: Control Of Kinetochore Mt Dynamicsmentioning
confidence: 99%